Refatoração com enfoque em portabilidade como estratégia de reúso em desenvolvimento de middleware para TV digital interativa - Sardinha, Eduardo Drumond (Universidade Federal de São Carlos, 2011)
Middleware for interactive digital TV systems are designed to provide convenient abstractions to overcome differences of hardware/software in order to improve the portability of applications. The development of a middleware implementation from scratch is a complex and costly task. To minimize this effort, software assets of existing implementations of these middleware can be reused through software reuse techniques. A refactoring process can be applied to existing middleware implementations to improve some software requirements such as modularity and reusability, in order to facilitate reuse of the middleware. This work presents an approach of refactoring focused on portability as a reuse strategy for the development of new instances of a digital TV middleware for new hardware platforms. The proposed approach is based on software portability concepts and construction characteristics of digital TV middleware. To evaluate the work, we present a case study with our experience of refactoring an implementation of the Brazilian digital TV system s middleware.
Keywords: Software; Reuso; Televisão digital; Middleware; Refatoração; Portabilidade; Digital TV; Middleware; Reuse; Refactoring; Portability; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO